2018
DOI: 10.1177/0748233718778993
|View full text |Cite|
|
Sign up to set email alerts
|

Toxic effects of imidacloprid combined with arsenic: Oxidative stress in rat liver

Abstract: Imidacloprid (IMI), a newer neonicotinoid insecticide, induces oxidative insult to hepatocytes due to the formation of reactive metabolites during hepatic metabolism. The present study aimed to determine the potentiating effect of arsenic (As) on IMI-induced hepatic damage in Wistar rats. Rats, randomly divided into eight groups with six in each, were subjected to daily oral administration for 28 days. Group I served as control; group II received IMI at the dose rate of 16.9 mg/kg body weight; groups III, IV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…Co-exposure to IMI and arsenic produced more pronounced fall in TTH level (63.8%) in renal tissue as compared to control ( Table 1 ). Similar decline in TTH level have also been reported in different visceral organs in arsenic exposed rats [ [46] , [47] , [48] ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Co-exposure to IMI and arsenic produced more pronounced fall in TTH level (63.8%) in renal tissue as compared to control ( Table 1 ). Similar decline in TTH level have also been reported in different visceral organs in arsenic exposed rats [ [46] , [47] , [48] ].…”
Section: Resultssupporting
confidence: 84%
“…The reduction in activities of these antioxidant enzymes might be either due to increased concentration of free radicals or decreased concentration of reduced glutathione a substrate for different antioxidant enzymes like GPx, GST and GR. Such pronounced alterations in different antioxidant parameters in different visceral organs of animals exposed concurrently to insecticides and metals have been reported [ 41 , [46] , [47] , [48] ].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The supernatant was collected separately and stored at − 20 °C for biochemical analysis. Total proteins were quantified using bovine serum albumin as standard and lipid peroxidation (LPO) was measured in terms of malondialdehyde (MDA) production following the thiobarbituric acid method [21]. Superoxide dismutase (SOD) and Catalase (CAT) activities were measured as per described by Dimo et al [22].…”
Section: Methodsmentioning
confidence: 99%
“…After this project, several studies in different regions of Pakistan reported as contamination of groundwater to a varying extent (below detection limit to 3090 µg/L). Arsenic concentrations in Kamchatka, New Zealand, Japan, Alaska, California, and Wyoming are high in the thermal waters, where black shales are common, but they are low in thermal waters from Hawaii and Iceland [11][12][13][14][15], where most of the rocks are geologically young basalts.…”
Section: Source Of Arsenic Exposurementioning
confidence: 99%